Financial development and economic growth: a study using generalized method of moments - Abdullah, Abu Bakar; Ibrahim, Saifuzzaman; Wan Ngah, Wan Azman Saini (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This study aims to examine the impact of financial development on economic growth in 53 countries. In order to account the effect of both banking sector and stock market, the estimation includes the level of development measures of these two sectors in one model. Adopting generalized method of moments (GMM), the findings suggest that both development in banking sector and stock market are significant in economic growth.